(untitled) (Fiep Bulletin - online, 2013)
The pedagogical practice is a diverse art that for decades has been directing the Physical Education professionals to build their own "garb" methodology, because the practice of a teacher can be influenced by several factors, such are their experiences and social experiences , professionals and intellectuals. Faced with this reality, the present study aims at evaluating the practice of physical education professionals who work in the early grades of elementary school of the municipal school teacher Rosália Freire in São Luís-MA and specific objectives, check the practice of these professionals within the teaching and learning process and emphasize the context in reflective practice. Field research is a qualitative and instruments used for assessment interviews were open-type and direct observations of physical education classes. Data analysis permeated the categories: Continuing education for teachers; school planning, reflection on own practice and concept of Physical Education. It was found that the teachers surveyed have just graduate and that despite the elaborate annual plan, not all follow. However, they seek to develop their practice within a theoretical context and practical reflective, thus believe that contribute to the development of physical, motor, cognitive and affective partner of his students. We conclude that the path of a well-developed pedagogical practice has been gradually covered by the teachers of this research, therefore, it is believed that the reflection of teaching practice can contribute to a better quality of teachers’ pedagogical action.